Lack of specificity of brain gangliosides in the modulation of lymphocyte activation. - Ryan, J. L. (Yale Journal of Biology and Medicine, 1985)
A potential role for glycolipid gangliosides to act as immunomodulating agents has been suggested. Most studies have employed brain gangliosides. We have systematically investigated highly purified murine brain gangliosides for their ability to modulate lymphocyte activation. All sialic acid classes of ganglioside inhibited lipopolysaccharide (LPS)-induced antibody secretion and all polysialated gangliosides inhibited LPS-induced DNA synthesis. Monosialated gangliosides had no effect on DNA synthesis induced by LPS. 8-BrcGMP-induced DNA synthesis was also inhibited, suggesting that a negative signal was delivered to B lymphocytes by co-cultivation with exogenous gangliosides. The lack of specificity with respect to sialic acid class observed in these studies suggests that further investigation of an immunomodulatory role for gangliosides focus on endogenous lymphocyte gangliosides.